MEMBANGUN LITERASI DIGITAL SISWA ERA NEW NORMAL - Gustina Erlianti; Marlini (Universitas Terbuka, 2022)
The purpose of this research is to build students' digital literacy through digital literacy training. The research method uses a quasi-experimental method with a one group pre-test and post-test design. The results of the pre-test and post-test showed an increase in students' understanding of digital literacy skills as indicated by an increase in the average score from 50.8 in the pre-test to 96.2 in the post-test. From these statistical results, it can be concluded that this digital literacy training activity is able to increase students' understanding of digital literacy skills in schools.